Do peacekeepers contain conflict? Insights from spatially disaggregated data - Bernd Beber (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
Mission-level data strongly suggests that peacekeeping operations offer a path toward conflict reduction. Recently available spatially disaggregated intra-mission data tells a more complex story. Peacekeepers are deployed, within missions, to where violence strikes, and they can prevent bloodshed, but the evidence for the latter is relatively brittle and contingent. This paper suggests that these findings at different levels of aggregation need not be contradictory, but that they constitute a puzzle that calls for continued efforts to improve and expand access to intra-mission data and a new evaluative approach that investigates a variety of adjustable mission components. I discuss the particular relevance of high-resolution geographic data for analyses of peacekeeping, comprehensively compile recent data collection efforts in this area, summarize their key findings and limitations, and outline a research frontier as it emerges from these datasets. – – Daten auf Landes- beziehungsweise Mandatsebene deuten stark darauf hin, dass Friedenssicherungseinsätze Konflikte entschärfen können. Allerdings zeigen in den letzten Jahren verfügbar gewordene räumlich aufgeschlüsselte Daten komplexere Zusammenhänge auf. Friedenstruppen werden innerhalb eines Landes zwar zu Gewaltherden entsandt. In manchen Fällen verhindern sie auch Blutvergießen. Aber die Indizien für einen regelmäßig gewaltreduzierenden Effekt sind brüchig und unbeständig. Dieses Papier schlägt vor, dass diese auf verschiedenen Aggregationsebenen angesiedelten Erkenntnisse nicht widersprüchlich sein müssen. Aber sie untermauern wie wichtig ein verbesserter und erweiterter Zugang zu einsatzinternen Daten und ein moderner Evaluierungsansatz, der einzelne Einsatzkomponenten untersucht, sind. Das Papier erörtert die Bedeutung hochauflösender geografischer Daten in der Analyse der Friedenssicherung, fasst Datenerhebungsbemühungen der letzten Jahre in diesem Bereich zusammen und skizziert wichtige Ergebnisse und die daraus folgende Forschungsfront.
Keywords: C81; D74; D78; 330; Peacekeeping operations; armed conflict; conflict containment; geographic spillovers; subnational data; data collection